Análise de resposta em frequência aplicada em transformadores de potência - Ezequiel Rabelo de Aguiar (2007)
This work deals with the frequency response analysis applied to power transformers. An approach was given to the measurement methods of the signature to support futures studies on the mechanical faults diagnosis. During the research, a measurement system was developed based on the Auto-Balanced Bridge method. The system performs tests and measurements of automatized form, by means of the frequency sweepings, and can be applied in field (substation). Also an equivalent circuit model was considered for the representation of the windingsin the frequency domain. It was based on measurements implemented in real power transformers and describes the main physical phenomena of the windings.